PA6/SILVER BLENDS: INVESTIGATION OF MECHANICAL AND ELECTROMAGNETIC SHIELDING BEHAVIOUR OF ELECTROSPUN NANOFIBERS - (:unkn) unknown (EGE UNIV, 2018)
PA6 nanofibrous membranes containing different amount of silver nanoparticles AgNP (0wt.%, 1wt.% and 2wt.%) were fabricated by a basic electrospinning set up that includes top to bottom feeding system. Morphology of the membranes was observed with SEM analysis. Headless and almost uniform nanofibers were yielded with the average fiber size ranged from 174 nm to 238 nm. Mechanical tests were also carried out in order to explore the tensile and elongation properties of the electrospun membranes, and it was noticed that the increased amount of AgNP in the blends decreased the mechanical performance of the membranes. In addition, fiber size distribution, feeding direction and agglomeration of AgNp were highly influent factors on both morphology and mechanical characteristics of the membranes. Electromagnetic shielding effectiveness (EMSE) of the electrospun nanofibrous membranes was determined according to the ASTM D4935-10 protocol by using coaxial transmission line measurement technique in the frequency range of 15-3000 MHz. It was observed that the membrane containing 2wt.% AgNP performed better EMSE than the others.
Keywords: Electrospinning; EMSE; nanofiber; nano silver; mechanical strength; POLYMER NANOFIBERS; SILVER; FABRICATION; NANOWIRES; SCAFFOLDS